Effects of inoculation and nitrogen fertilizer on soybean in western Nigeria - Kang, B.T. (1975)
The effect of inoculation and added nitrogen fertilizer on soybean variety TK-5 were studied in pot and field experiments. In the former bean yields with IARI and CB 1809 inoculants were better than with Nitragin-S. In the field experiment, inoculation alone was inadequate to supply the nitrogen need of the crop, 30 kg. N/ha. being needed with inoculation, and 60 kg. N/ha. without inoculation, for maximum yield. Higher nitrogen application, combined with inoculation, increased dry matter, N-uptake, bean yield, pod number, bean weight and nitrogen content of seed. Oil content of the seeds decreased with inoculation and nitrogen application